Aqueous zinc ion battery electrolyte additive capable of forming organic / inorganic hybrid SEI membrane and electrolyte

By using organic compounds with pyridine, fluorine atoms, and aldehydes as electrolyte additives in the zinc -ion battery of the water system as an electrolyte additive to form a gradient organic/inorganic hybrid SEI film, solving the problem of the growth and side effects of zinc negative polar crystals, significantly improved improvement The cycle stability and safety of the battery.

CN119381594APending Publication Date: 2025-01-28HUAIYIN TEACHERS COLLEGE
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411746838.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-02
Publication Date
2025-01-28

AI Technical Summary

Technical Problem

During the charging and discharging process of aqueous zinc-based zinc ion batteries, the growth and side reactions of zinc negative electrode dendrites occur frequently, resulting in cycle stability and safety issues.

Method used

The organic compound with pyridine, fluorine atom, and aldehydes is used as an electrolyte additive, which can form a gradient organic/inorganic hybrid SEI film in situ to inhibit the growth and side reactions of the chinetic crystal.

Benefits of technology

By forming a gradient organic/inorganic hybrid SEI film, the cycle stability and safety of the battery are significantly improved, the cycle life of the battery is extended, and the energy density and power density of the battery are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119381594A_ABST
    Figure CN119381594A_ABST
Patent Text Reader

Abstract

The invention discloses an aqueous zinc ion battery electrolyte additive capable of forming an organic / inorganic hybrid SEI membrane and an electrolyte. The additive contains pyridine rings, fluorine atoms and aldehyde groups. The additive can be adsorbed on the surface of zinc, can be spontaneously decomposed in the charging and discharging process, and can form a gradient organic / inorganic hybrid SEI film layer together with an electrolyte, an outer-layer SEI film component is mainly an organic component, an inner-layer SEI film component is mainly an inorganic component, the SEI film layer can isolate direct contact between zinc and water, the hydrogen evolution process is inhibited, and the service life of the SEI film layer is prolonged. Meanwhile, transmission of zinc ions is promoted. According to the additive, dendrite-free growth and side reaction inhibition of the zinc negative electrode are realized, and the cycle life of the battery is prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to an aqueous zinc ion battery electrolyte additive and an electrolyte capable of forming an organic / inorganic hybrid SEI film, belonging to the technical field of batteries and battery electrolytes. Background Art

[0002] As global energy shortages and climate change become increasingly serious, the development of safe, efficient and sustainable energy storage technologies has become a top priority. The shortage of traditional fossil energy and environmental pollution have prompted people to seek the widespread application of renewable energy, while the intermittent nature of renewable energy poses a huge challenge to the stability of the power grid. Therefore, building a more stable and efficient smart grid has become an important research direction. Aqueous zinc-ion batteries have shown broad application prospects in the field of new energy storage due to their high theoretical specific capacity, abundant resources, environmental friendliness and high safety. However, aqueous zinc-ion batteries still face many challenges in practical applications. First, the metal zinc negative electrode has problems such as dendrite growth and side reactions (such as hydrogen evolution reaction and electrode corrosion) during the charging and discharging process, which seriously restrict the cycle stability and reversibility of the battery. Dendrite growth not only causes battery short circuit, but also may cause safety problems; while hydrogen evolution reaction and electrode corrosion will reduce the coulombic efficiency and cycle life of the battery.

[0003] In order to overcome these challenges, researchers have proposed a variety of strategies, among which optimizing the electrolyte formulation and introducing electrolyte additives is a common and efficient strategy. Electrolyte additives can significantly improve the stability and cycle life of aqueous zinc-ion batteries by regulating the double layer near the negative electrode surface, improving the solvation structure, and inhibiting side reactions and dendrite growth. At present, a variety of effective electrolyte additives have been discovered, including polymers, organic molecules, ionic compounds, and bio-inspired additives. The mechanisms of action of these additives vary, but most of them focus on regulating the surface properties of the negative electrode, optimizing the solvation structure, and inhibiting side reactions. However, despite significant progress in the study of electrolyte additives, there are still many problems that need to be solved. For example, the mechanism of the influence of the molecular configuration of additives on battery performance has not been fully elucidated; the cost and environmental friendliness of additives still need to be further optimized; how to integrate multiple functions into one additive. Therefore, future research needs to continue to explore the mechanism of action of electrolyte additives, develop new and efficient additives, and promote the commercialization of aqueous zinc-ion batteries. Summary of the invention

[0004] The purpose of the present invention is to provide an aqueous zinc ion battery electrolyte additive capable of in-situ forming a gradient organic / inorganic hybrid SEI film, an electrolyte having the additive, and an application thereof, so as to solve the cycle stability and safety problems caused by zinc negative electrode dendrite growth and frequent side reactions in the prior art during the charge and discharge process of zinc ion batteries. The additive integrates a variety of functions that are beneficial to improving battery performance through its unique molecular structure, providing a new solution for the development of aqueous zinc ion batteries.

[0005] In order to achieve the above object, the technical solution adopted by the present invention is: An aqueous zinc ion battery electrolyte additive capable of in-situ forming a gradient organic / inorganic hybrid SEI film, the additive being an organic compound having a pyridine ring, a fluorine atom and an aldehyde group.

[0006] Preferably, the fluorine atom or aldehyde group in the additive is directly or indirectly connected to different carbon atoms on the pyridine ring.

[0007] Preferably, the additive is one or more of 2-fluoropyridine-3-carboxaldehyde, 2-fluoropyridine-4-carboxaldehyde, 2-fluoropyridine-5-carboxaldehyde, 3-fluoropyridine-2-carboxaldehyde, 3-fluoropyridine-4-carboxaldehyde and derivatives of the above organic compounds.

[0008] An aqueous zinc ion battery electrolyte capable of in-situ forming a gradient organic / inorganic hybrid SEI film comprises any of the above-mentioned electrolyte additives.

[0009] Preferably, the electrolyte is a zinc salt electrolyte.

[0010] Preferably, in the zinc salt electrolyte, the zinc salt is any one of zinc sulfate, zinc chloride, zinc acetate, and zinc trifluoromethanesulfonate.

[0011] Preferably, in the zinc salt electrolyte, the concentration of zinc salt is 1-3 mol / L.

[0012] Preferably, in the electrolyte, the concentration of the additive is 0.01-0.9 g / L.

[0013] An aqueous zinc ion battery capable of in-situ forming a gradient organic / inorganic hybrid SEI film comprises any of the above-mentioned electrolyte additives.

[0014] An aqueous zinc ion battery, wherein the surface of the zinc electrode is covered with an SEI film, wherein the SEI film is composed of organic fluorine and inorganic fluorine materials, and the proportion of organic fluorine gradually increases from the inner layer close to the zinc electrode to the outer layer; the organic fluorine refers to an organic fluorine compound containing a CF bond, and the inorganic fluorine refers to ZnF 2 .

[0015] The beneficial effects of the present invention are: The role of additives in this application is reflected in the following aspects, specifically: 1. During the charge and discharge cycle, the additives will spontaneously adsorb on the electrode surface and then decompose with the electrolyte to form a gradient organic / inorganic hybrid SEI film; 2. The outer layer of the SEI film is mainly composed of organic components, which is beneficial to isolate the direct contact between water and the zinc negative electrode, inhibit the hydrogen evolution reaction, and also help guide the uniform deposition of zinc ions; 3. The inner layer is mainly composed of inorganic substances (ZnF 2 , ZnS, ZnO, ZnCO 3 etc.), which is beneficial to improve the transmission efficiency of zinc ions and reduce the interface resistance.

[0016] The impacts on zinc-ion batteries are mainly as follows: 1. Improve battery cycle life: By inhibiting the dendrite growth and side reactions of the zinc negative electrode, the cycle stability and reversibility of the battery are significantly improved, and the cycle life of the battery is extended; 2. Enhance battery safety: reduce the risk of battery short circuit caused by dendrite growth and improve battery safety performance; 3. Improve battery performance: The formation of fluorine-containing SEI film promotes the transmission of zinc ions, reduces interface resistance, and improves the energy density and power density of the battery; 4. Environmentally friendly: The additive of the present invention has a stable molecular structure and is not easy to decompose to produce harmful substances, thus meeting environmental protection requirements.

[0017] In summary, the aqueous zinc ion battery electrolyte additive of the present invention provides a new idea and method for improving the performance of aqueous zinc ion batteries through its unique molecular structure design and functional integration, and has important application value and market prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 The etching XPS of the electrode surface after the electrolyte in Example 1 was cycled 30 times, (a) F 1s, (b) N 1s, (c) S 2p; Figure 2 The etching XPS of the electrode surface after 30 cycles of the electrolyte in Example 1, (a) O 1s, (b) C 1s, (c) Zn 2p; Figure 3 are the ion migration numbers of the electrolytes in Example 1 and Comparative Example 1 respectively; Figure 4The comparison of hydrogen production changes detected by electrochemical in-situ gas chromatography during electroplating of the electrolyte in Example 1 and Comparative Example 1 is shown in (a) the chromatogram of Comparative Example 1, (b) the chromatogram of Example 1, and (c) the comparison of hydrogen production; Figure 5 Activation energy diagrams of the electrolytes in Example 1 and Comparative Example 1, respectively; Figure 6 The dendrite growth conditions monitored by in-situ optical microscope of the electrolyte in Example 1 and Comparative Example 1 respectively; Figure 7 The figures are rate performance test diagrams of symmetrical batteries using the electrolytes in Example 1 and Comparative Example 1 respectively; Figure 8 The symmetrical battery using the electrolytes in Example 1 and Comparative Example 1 at 1 mA / cm 2 @ 1 mAh / cm 2 Long cycle life diagram below; Fig. 9 For the symmetrical battery using the electrolytes in Example 1 and Comparative Example 1 at 2 mA / cm 2 @ 2 mAh / cm 2 Long cycle life diagram below; Fig.10 The self-discharge results of symmetrical batteries using the electrolytes in Example 1 and Comparative Example 1 respectively; Fig.11 The coulombic efficiency of the zinc-copper battery using the electrolytes in Example 1 and Comparative Example 1 respectively. DETAILED DESCRIPTION Example 1

[0019] Preparation of aqueous zinc ion battery electrolyte containing additives (1) 2 mol of ZnSO 4 Dissolve in deionized water and shake until completely dissolved to prepare 2 mol / L ZnSO 4 Aqueous electrolyte.

[0020] (2) Add 2-fluoropyridine-5-carboxaldehyde to the aqueous electrolyte prepared above, and stir magnetically until it is completely dissolved to prepare an aqueous electrolyte containing 0.3 g / L of the additive.

[0021] Comparative Example 1 The electrolyte is 2 M ZnSO 4 .

[0022] A 100 μm thick zinc foil was cut into 12 mm diameter discs and washed and dried with deionized water and anhydrous ethanol as a zinc negative electrode. The electrolytes were the aqueous zinc ion battery electrolyte obtained in Example 1 and the 2 M ZnSO 4 , using glass fiber as the separator and other conditions being the same, button cells were assembled for testing.

[0023] like Figure 1 and Figure 2 The composition of the SEI film on the surface of the zinc sheet using the electrolyte of Example 1 after 30 cycles was analyzed by etching XPS. Figure 1 In the middle a region, the surface obviously contains more CF bonds and less ZnF 2 , and with the increase of etching depth, the CF bonds are significantly reduced, and ZnF 2 The components of the surface increase, which indicates that the surface is composed of more organic fluorine and less inorganic fluorine, while the interior is just the opposite; Figure 1 In the middle b area, N is composed of organic elements, and it is obvious that the organic composition decreases from the outside to the inside; ZnS is also less on the surface and more inside ( Figure 1 middle c area); Figure 2 The contents of O, C, and Zn elements also further confirmed the formation of a gradient organic / inorganic hybrid SEI film after cycling.

[0024] Figure 3 The ion migration number of zinc ions was measured, and it can be seen that the ion migration number of zinc ions in the electrolyte in Example 1 is significantly higher than that in Comparative Example 1, which indicates that the gradient organic / inorganic hybrid SEI film promotes the transmission of zinc ions; Figure 4 The production of hydrogen during the electroplating process was measured. It can be seen that after using the electrolyte of Example 1, the production of hydrogen decreased significantly. This is because the gradient organic / inorganic hybrid SEI film isolates the direct contact between zinc and the electrolyte, thereby inhibiting the hydrogen evolution process. The activation energy ( Figure 5 ), the activation energy in Example 1 is significantly lower, which is due to the fact that the gradient organic / inorganic hybrid SEI film promotes the desolvation process of hydrated zinc ions, which is mutually verified by the increase in the zinc ion migration number. Figure 6 The zinc deposition process was further observed using an in-situ optical microscope. It can be seen that after using the electrolyte of Example 1, the zinc deposition was more uniform and dense, while when using the electrolyte of Comparative Example 1, dendrites and irregular loose deposition were obviously present in the zinc deposition process, which indicates that the gradient organic / inorganic hybrid SEI film formed by the addition of additives inhibits the growth of dendrites.

[0025] The battery rate results are as follows Figure 7 As shown by Figure 1It can be seen that at different current densities, the polarization potential of the zinc-zinc battery containing 2-fluoropyridine-5-carboxaldehyde additive is close to that of Comparative Example 1 at different current densities, indicating that the addition of 2-fluoropyridine-5-carboxaldehyde additive does not hinder the deposition of zinc ions, and Comparative Example 1 short-circuited after 60 h, while Example 1 still did not short-circuit after 150 h.

[0026] Long-term cycle stability Figure 8 As shown in Example 1, the zinc-zinc battery containing 2-fluoropyridine-5-carboxaldehyde additive in the electrolyte has a 2 @1 mAh / cm 2 The cycle life of the Zn-Zn battery is more than 3000 h, while the life of the Zn-Zn battery without additives in the electrolyte (Comparative Example 1) is less than 200 h. Even at higher current density and higher surface capacity of 2 mA / cm 2 @2 mAh / cm 2 ( Fig. 9 ), the zinc-zinc battery containing 2-fluoropyridine-5-carboxaldehyde additive in the electrolyte in Example 1 can still achieve a lifespan of nearly 1000 h.

[0027] The influence of self-corrosion is further analyzed, such as Fig.10 As shown, the zinc-zinc battery containing 2-fluoropyridine-5-carboxaldehyde additive in the electrolyte in Example 1 achieved a life of more than 2000 h during continuous charge and discharge and static process, while the zinc-zinc battery in Comparative Example 1 without additive added to the electrolyte short-circuited after 200 h, which indicates that the 2-fluoropyridine-5-carboxaldehyde additive inhibits the self-corrosion of zinc.

[0028] In an asymmetric cell (zinc-copper cell, zinc as the negative electrode), the coulombic efficiency during zinc plating and stripping was tested as follows: Fig.11 After adding 2-fluoropyridine-5-carboxaldehyde additive to the electrolyte (Example 1), the coulombic efficiency was close to 100% during 600 repeated electroplating and stripping processes; while the coulombic efficiency was close to 100% when 2 M ZnSO 4 When used as an electrolyte (Comparative Example 1), the coulombic efficiency dropped sharply after dozens of cycles, followed by a short circuit. These results show that the 2-fluoropyridine-5-carboxaldehyde additive can significantly enhance the stability of the zinc negative electrode. Example 2

[0029] Preparation of aqueous zinc ion battery electrolyte containing additives (1) 2 mol of ZnSO 4 Dissolve in 1 L of deionized water and shake until completely dissolved to prepare 2 mol / L ZnSO 4 Aqueous electrolyte.

[0030] (2) Add 2-fluoropyridine-5-carboxaldehyde to the aqueous electrolyte prepared above, and stir magnetically until it is completely dissolved to prepare an aqueous electrolyte containing 0.5 g / L of the additive.

[0031] Assemble the Zn-Zn battery and test its cycling stability at 1 mA / cm 2 @1mAh / cm 2 The lower cycle life exceeds 1500h. Example 3

[0032] Preparation of aqueous zinc ion battery electrolyte containing additives (1) 2 mol of ZnSO 4 Dissolve in 1 L of deionized water and shake until completely dissolved to prepare 2 mol / L ZnSO 4 Aqueous electrolyte.

[0033] (2) Add 2-fluoropyridine-3-carboxaldehyde to the aqueous electrolyte prepared above, and stir magnetically until it is completely dissolved to prepare an aqueous electrolyte containing 0.5 g / L of the additive.

[0034] Assemble the Zn-Zn battery and test its cycling stability at 1 mA / cm 2 @1mAh / cm 2 The lower cycle life exceeds 1000h.

[0035] The above is only a preferred implementation of the patent of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the patent of the present invention. These improvements and modifications should also be regarded as the scope of protection of the patent of the present invention.

Claims

1. An aqueous zinc ion battery electrolyte additive capable of in-situ forming a gradient organic / inorganic hybrid SEI film, characterized in that: The additive is an organic compound having a pyridine ring, a fluorine atom and an aldehyde group.

2. The aqueous zinc ion battery electrolyte additive according to claim 1, characterized in that: The fluorine atom and the aldehyde group in the additive are directly or indirectly connected to different carbon atoms on the pyridine ring.

3. The aqueous zinc ion battery electrolyte additive according to claim 1, characterized in that: The additive is one or more of 2-fluoropyridine-3-carboxaldehyde, 2-fluoropyridine-4-carboxaldehyde, 2-fluoropyridine-5-carboxaldehyde, 3-fluoropyridine-2-carboxaldehyde, 3-fluoropyridine-4-carboxaldehyde and derivatives of the above organic compounds.

4. An aqueous zinc ion battery electrolyte, characterized in that: Contains the electrolyte additive described in any one of claims 1-3.

5. The aqueous zinc ion battery electrolyte according to claim 4, characterized in that The electrolyte is a zinc salt electrolyte.

6. The aqueous zinc ion battery electrolyte according to claim 5, characterized in that In the zinc salt electrolyte, the zinc salt is any one of zinc sulfate, zinc chloride, zinc acetate and zinc trifluoromethanesulfonate.

7. The aqueous zinc ion battery electrolyte according to claim 6, characterized in that: In the zinc salt electrolyte, the concentration of zinc salt is 1-3 mol / L.

8. The aqueous zinc ion battery electrolyte according to claim 4, characterized in that: In the electrolyte, the concentration of the additive is 0.01-0.9 g / L.

9. An aqueous zinc ion battery, characterized in that: Contains the electrolyte additive described in any one of claims 1-3.

10. An aqueous zinc ion battery, characterized in that: The surface of the zinc electrode is covered with a SEI film, which is composed of organic fluorine and inorganic fluorine materials. The proportion of organic fluorine gradually increases from the inner layer close to the zinc electrode to the outer layer; the organic fluorine refers to an organic fluorine compound containing a CF bond, and the inorganic fluorine refers to ZnF2.

Citation Information

Cited By

  • Zinc ion battery electrolyte with in-situ induced double-layer solid electrolyte interface and application of zinc ion battery electrolyte

    CN121035381A